«Fear and Tremor» in Kierkegaard and Kant - Ferdori, Donato (Governare la paura. Journal of interdisciplinary studies, 2011)
For Kierkegaard it is inevitable to deal with anguish, even though it is linked to evil, intended from a moral and theological point of view. Anguish can be dominated or even transformed into an ally if one leads a spiritual life. If one dominates anguish, one no longer has fears, either. In Kierkegaard’s thought we find a model of life and management of anguish that transcends the traditional dichotomies ethics/religion, eros/agape and can be compared to Kantian anthropocentric theology. But there is “another Kierkegaard”, one who is internally divided and dominated by anguish, and this is at the antipodes of Kant. The essay shows how this duplicity in Kierkegaard’s thought can be best understood from the perspective of Kantian ethical hermeneutics.